2021
DOI: 10.2147/idr.s295077
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Nutritional Status in the Prognostic Analysis of Patients with AIDS-Related Lymphoma

Abstract: Objective Many studies have suggested that indexes of nutritional status, such as body mass index (BMI), serum albumin (ALB), serum pre-albumin (PA), and hemoglobin, may be used as risk factors for the prognosis of HIV or lymphoma. Therefore, this study aimed to retrospectively analyze and explore the value of nutritional status in the prognostic assessment of patients with AIDS-related lymphoma (ARL). Methods In this retrospective study, the clinical data of 69 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(8 reference statements)
2
10
0
Order By: Relevance
“…Although baseline T-cell status and age have been associated with the response of ratio restoration, ALB levels were not reported as such a variable. At present, several studies imply that markers of nutritional condition, such as BMI, ALB, and HGB, may be used as risk indicators for the prognosis of HIV/AIDS patients [32], and that hypoproteinemia is usually one of the typical characteristics of cachexia [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although baseline T-cell status and age have been associated with the response of ratio restoration, ALB levels were not reported as such a variable. At present, several studies imply that markers of nutritional condition, such as BMI, ALB, and HGB, may be used as risk indicators for the prognosis of HIV/AIDS patients [32], and that hypoproteinemia is usually one of the typical characteristics of cachexia [33].…”
Section: Discussionmentioning
confidence: 99%
“…ARL patients have a higher risk of immunode ciency and malnutrition. Studies have shown that low serum albumin levels are closely related to the poor prognosis of patients [13,14]. Studies have found that hypoalbuminemia are closely related chronic in ammation and may be related to cytokines interleukin-6 and tumor necrosis factor.…”
Section: Page 6/16mentioning
confidence: 99%
“…That suggest that ARL patients have poor nutritional status, heavy tumor burden, hypoxia, and high tumor resistance to chemoradiotherapy. Many studies have shown that low levels of albumin or high levels of LDH are associated with poor prognosis [11,13,14,17]. ARL patients should also pay attention to the schedule and timing of antiviral therapy and chemotherapy.…”
Section: Page 6/16mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several biomarkers have been suggested to be related to the prognosis of ARL, including IPI, age-adjusted IPI, CD4 + T cells count, age, Eastern Cooperative Oncology Group performance status (ECOG PS), chemotherapy, lactate dehydrogenase (LDH), Epstein- barr virus deoxyribonucleic acid (EBV DNA), hepatitis C virus, the Burkitt/Burkitt-like lymphoma subtype, history of clinical AIDS, and expression of B-cell lymphoma-2 (BCL2), cluster of differentiation 4 (CD44), Protein 53 (p53) and Immunoglobulin M (IgM) [ 10 15 ]. Alternatively, recent immunosuppression and prolonged HIV viraemia have important independent roles in the development of ARL [ 16 ].…”
Section: Introductionmentioning
confidence: 99%